DETERMINANTS OF FINANCIAL DISTRESS: REVIEW OF THE ASPECTS OF PROFITABILITY, LIQUIDITY, LEVERAGE, AND ACTIVITY - Umam, Danang Choirul; Yusuf, Yusuf (Asosiasi Dosen Muda Indonesia, 2024)
This research aims to determine the determinants of financial distress in wholesale and retail trade subsector companies listed on the Indonesian Stock Exchange. In this research, financial distress is measured by Zscore, profitability is measured by Return on Assets, liquidity is measured by Current Assets, Debt measures leverage to Assets Ratio, and Total Assets Turnover measures activity. The research methods used in this research are descriptive and verification methods. The sample for this research was 29 companies obtained based on a purposive sampling technique with a five-year research period of 5 years, so the observation data totalled 145. The statistical analysis used is a linear regression analysis of panel data with time lag using the Eviews 10—Tektik program panel data linear regression estimation using the Fixed Effect Model. The coefficient test results show that profitability hurts financial distress, liquidity does not affect financial distress, leverage hurts negatively, and activity positively affects financial distress.